Pandemic effects on social media marketing behaviors in India - Nicholas Mason; Matt Brown; Kevin Mason; John Narcum (Cogent Business & Management, 2021)
This research examined the effects of the COVID-19 pandemic on social media marketing in India. There is little research on the impact of a pandemic on consumer behaviors. To address this gap, this exploratory study surveyed Indian consumers' social media behaviors. Observations from 313 Indian consumers were collected to compare how their social media behaviors for consumer decision-making have changed since the COVID-19 pandemic started. A Wilcoxon signed-rank test was used to test mean differences in social media behaviors prior to and after the COVID-19 pandemic began. The findings demonstrated increased usage of social media as a tool for consumer decision-making. With the global reach of the COVID-19 pandemic, the implications of a growing prominence of social media in consumer-decision making are likely relevant to most nations. Recommendations for the use of social media as a marketing tool are provided.
Keywords: 650; COVID-19; India social media marketing; consumer decision-making